Abnormal megakaryopoiesis and platelet function in cyclooxygenase-2-deficient mice - Barbieri, Silvia S.; Petrucci, Giovanna; Tarantino, Eva; Amadio, Patrizia; Rocca, Bianca; Pesce, Maurizio; Machlus, Kellie R.; Ranelletti, Franco O.; Gianellini, Sara; Weksler, Babette B.; Italiano, Joseph E., Jr.; Tremoli, Elena (Thrombosis and Haemostasis, 2015)
Previous studies suggest that cyclooxygenase-2 (COX-2) might influence megakaryocyte (MK) maturation and platelet production in vitro. Using a gene deletion model, we analysed the effect of COX-2 deficiency on megakaryopoiesis and platelet function. COX-2-/- mice (10–12 weeks old) have hyper-responsive platelets as suggested by their enhanced aggregation, TXA2 biosynthesis, CD62P and CD41/CD61 expression, platelet-fibrinogen binding, and increased thromboembolic death after collagen/epinephrine injection compared to wild-type (WT). Moreover, increased platelet COX-1 expression and reticulated platelet fraction were observed in COX-2-/- mice while platelet count was similar to WT. MKs were significantly reduced in COX-2-/- bone marrows (BMs), with high nuclear/cytoplasmic ratios, low ploidy and poor expression of lineage markers of maturation (CD42d, CD49b). However, MKs were significantly increased in COX-2-/- spleens, with features of MK maturation markers which were not observed in MKs of WT spleens. Interestingly, the expression of COX-1, prostacyclin and PGE2 synthases and prostanoid pattern were modified in BMs and spleens of COX-2-/- mice. Moreover, COX-2 ablation reduced the percentage of CD49b+ cells, the platelet formation and the haematopoietic stem cells in bone marrow and increased their accumulation in the spleen. Splenectomy decreased peripheral platelet number, reverted their hyper-responsive phenotype and protected COX-2-/- mice from thromboembolism. Interestingly, fibrosis was observed in spleens of old COX-2-/- mice (28 weeks old). In conclusion, COX-2 deletion delays BM megakaryopoiesis promoting a compensatory splenic MK hyperplasia, with a release of hyper-responsive platelets and increased thrombogenicity in vivo. COX-2 seems to contribute to physiological MK maturation and pro-platelet formation.
Keywords: COX-2; platelets; thrombosis; megakaryocytes